Global analysis of gene translation - Tofilon, Philip (Henry Stewart Talks, 2009)
Radiation-induced gene expression has long been considered to play a role in determining cellular radioresponse, Analyses of single genes and whole genomes indicate that radiation-induced changes at the mRNA level do not correlate with changes in corresponding proteins, Microarray analysis of polysome-bound RNA indicates that radiation modifies the translational activity of mRNA subpopulations, which correlates with protein products, Gene translation is considerably more susceptible to radiation-induced changes than is the transcriptome, Defining the genes whose translation is modified by radiation may provide an approach for identifying critical proteins and pathways that serve as determinants of radiosensitivity
Archived at 2021/02/25